Determination of Reference Dose (RfD) of Mercury Exposure Based on NOAEL Mercury - Pudji Rahmawati, Abdul Rohim Tualeka,Mahmud Aditya Rifky, Juliana Jalaludin, Syamsiar S Russeng,; Indri H Susilowati, Ahsan Ahsan, (Opción, 2019)
This study aimed to determine the RfD from mercury exposure in Bulawa Subdistrict in Bone Bolango District using NOAEL mercury in white mice and body weight and height of Indonesians who were exposed to mercury. This was an observational study with a cross-sectional design using manual quantitative data analysis methods. As a result, the average mercury concentration in respondents’ drinking water and fish consumed was 0.000478 mg/L and 0.0298 mg/kg. In conclusion, the average mercury concentration in respondents’ drinking water and fish consumed is still below the threshold limit value set by the national standard for mercury concentrations.